Transcriptome Analysis and RNA Interference Reveal GhGDH2 Regulating Cotton Resistance to Verticillium Wilt by JA and SA Signaling Pathways - Xiong, Xian-Peng; Sun, Shi-Chao; Zhu, Qian-Hao; Zhang, Xin-Yu; Liu, Feng; Li, Yan-Jun; Xue, Fei; Sun, Jie (Frontiers in Plant Science, 2021)
Verticillium wilt, caused by Verticillium dahliae, is one of the most damaging and widespread soil-borne cotton diseases. The molecular mechanisms underlying the cotton defense against V. dahliae remain largely elusive. Here, we compared the transcriptomic differences between Upland cotton (Gossypium hirsutum L.) cultivar resistant (Shidalukang-1 or HR) or susceptible (Junmian 1 or HS) to V. dahliae at multiple time points after V. dahliae inoculation, identified 2010 and 1275 differentially expressed genes in HR and HS, respectively. Plant hormone signal transduction-related genes were enriched in HR, whereas genes related to lignin biosynthesis were enriched in both HR and HS. Weighted gene co-expression network analysis using the 2868 non-redundant genes differentially expressed between the V. dahliae infected and uninfected samples in HR or HS identified 10 different gene network modules and 22 hub genes with a potential role in regulating cotton defense against V. dahliae infection. GhGDH2, encoding glutamate dehydrogenase, was selected for functional characterization. Suppressing the expression level of GhGDH2 by virus-induced gene silencing led to inhibition of the salicylic acid biosynthesis/signaling pathways and activation of the jasmonic acid biosynthesis/signaling pathways, resulted in increased JA content and reduced SA content in cotton roots, consequently enhanced V. dahliae resistance. Our finding provides new insights on the molecular mechanisms of cotton resistance to V. dahliae infection and candidate genes for breeding V. dahliae resistance cotton cultivars by genetic modification.